Comparison of Maximum Fingertip Force Distribution in Cylindrical Grasping Between Healthy Adults and Patients With Spinal Cord Injury - Jisun Hwang; Jae Sun Ree; Seonhong Hwang (Korean Research Society of Physical Therapy, 2022)
Background: It is known that hand strength and fingertip force are used as an indicator of muscle strength and are also highly related to the various chronic symptoms and even lifespan. To use the individual fingertip force (IFF) as a quantitative index for clinical evaluation, the IFF should be measured and analyzed with various variables from various subjects, such as the normal range of fingertip force and the difference in its distribution by disease. Objects: We tried to measure and analyze the mean maximum IFF distribution during grasping a cylindrical object in healthy adults and patients with spinal cord injury (SCI). Methods: Five Force-sensitive resistor (FSR) sensors were attached to the fingertips of 24 healthy people and 13 patients with SCI. They were asked to grip the object three times for five seconds with their maximum effort. Results: The mean maximum IFF of the healthy adult group's thumb, index, and middle finger was similar statistically and showed relatively larger than IFF of the ring and small finger. It is a 3-point pinch grip pattern. All fingertip forces of patients with SCI decreased by more than 50% to the healthy group, and their IFF of the middle finger was relatively the largest among the five fingertip forces. The cervical level injured SCI patients showed significantly decreased IFFs compared to thoracic level injured SCI patients. Conclusion: We expect that this study results would be helpful for rehabilitation diagnosis and therapy goal decision with robust further study.